alpha-Actinin from chicken gizzard: at low temperature, the onset of actin-gelling activity correlates with actin bundling. - Grazi, E (1994)
The effect of alpha-actinin from chicken gizzard on the properties of F-actin solutions at 37 degrees C and at 4 degrees C was investigated. Beside the well-known increase of the gelling activity of alpha-actinin, it was found that lowering temperature to 4 degrees C: (a) modifies the shape of the alpha-actinin-F-actin binding isotherm; (b) increases the light scattering of the alpha-actinin-F-actin mixtures; (c) induces the formation of ribbons and bundles of F-actin. It was also observed that, by warming to 37 degrees C, the bundles of F-actin formed at 4 degrees C were dissociated into quasi-parallel actin filaments running at a distance of 25-42 nm from each other. On subsequent cooling to 4 degrees C, these parallel filaments were rapidly assembled into bundles. As at 37 degrees C, alpha-actinin displays a potent gelling activity on bundles but not on filaments of actin, and as the gelling activity at 4 degrees C is accompanied by the formation of actin bundles, it is concluded that actin bundling is a necessary condition to promote the actin-gelling activity.